A low-palladium acidic HER catalyst based on W, Mo, N co-doped carriers, a preparation method and application thereof
Patent Information
- Application Number
- CN202310131379.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-17
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2043-02-17
AI Technical Summary
本发明的制备方法工艺简单、容易实现、易于实现大规模生产,成本低,且所制备的低铂HER催化剂在酸性电解液中具有优异的HER电化学性能和稳定性。在0.5M H2SO4下测试,与商业铂碳相比具有更低的过电位,具有比商业铂碳更优异的稳定性。所制备的低铂催化剂在Pt含量仅为商业铂碳1/7的情况下,仍然具有优于商业铂碳的电催化性能。掺杂到碳黑中的W,Mo纳米团簇与Pt颗粒形成异质结构,使得Pt与W、Mo之间存在协同效应,优化了催化剂在催化过程中的电子结构和电荷传递/传质性能,并且,协同效应可以有效地降低氢在催化剂表面的吸附能,使氢的吸附吉布斯自由能趋近于零的理想值,进而促进了催化剂的HER催化性能。
Smart Images

Figure CN116334682B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of water electrolysis, specifically relating to a low-Pt acidic HER catalyst based on a W, Mo, N co-doped support, its preparation method, and its application. Background Technology
[0002] Hydrogen (H2) is a potential alternative to fossil fuels and a promising clean energy source for the 21st century. However, even today, nearly 96% of commercial hydrogen production still occurs through methods that consume non-renewable fossil fuels, such as steam reforming of natural gas, which always generates significant amounts of carbon dioxide. Hydrogen production via electrocatalysis (HER) is a promising approach that could replace current fossil fuel-based energy systems that emit carbon dioxide, while simultaneously enabling efficient energy conversion and storage of intermittent energy sources such as wind and solar power. However, in acidic environments, due to limitations in reaction kinetics and stability, the noble metal Pt is still widely used as a HER catalyst. The high cost and scarcity of Pt, along with its poor stability in corrosive electrolytes, severely limit its commercial application. Therefore, developing low-platinum HER catalysts that reduce catalyst loading while maintaining high activity is crucial.
[0003] To develop high-performance Pt catalysts, much research has focused on two main aspects. One is suppressing Pt aggregation by using dispersants or employing complex catalyst preparation processes to strictly control the size of Pt particles, thereby improving catalyst performance. The other aspect involves modifying the Pt catalyst support, including using materials such as MOFs and COFs, or carbon materials like graphene and carbon nanotubes, or pretreating the carbon support to enhance catalyst performance.
[0004] In recent years, Pt nanoparticles supported on carbon-based composite materials have become a promising method to enhance their HER catalytic activity. (1) In recent years, a large number of studies have focused on the preparation of Pt single-atom catalysts. The preparation of single-atom catalysts often involves a relatively complex catalyst preparation process, or the confinement effect of MOF precursor materials is used to prepare highly dispersed Pt catalysts. (2) There are also relatively many studies on Pt alloy catalysts with transition metals (e.g., Co, Ni, etc.). Due to the sintering and surface roughening of the alloying process of Pt alloy catalysts, it is not easy to control the synthesis of alloy catalysts. (3) Heteroatom doping modification of carbon supports (N, S, P, F, Se, etc.) is also a relatively common preparation method. Through heteroatom modification and doping, the defects on the carbon support increase, providing more anchoring sites for Pt loading, thereby promoting the catalytic performance of the catalyst.
[0005] CN111298790A discloses a method for preparing a hydrogen evolution reaction catalyst of Pt atom cluster supported WO3 nanosheets. This patent involves a two-step reduction process in the synthesis process and uses a hydrothermal reaction to prepare the catalyst, which is difficult to achieve in large-scale industrial production.
[0006] CN114649538A discloses a method for preparing an electrocatalyst for methanol electrolysis to produce hydrogen. This method uses nitrogen-phosphorus-doped carbon molybdenum telluride as a composite support and platinum-based nanoparticles as the catalyst loading, which can be used in acidic methanol electrolysis reactions. This patent first synthesizes a Mo-MOF material, mixes it with tellurium powder, and then pyrolyzes it at high temperature to obtain a modified support, followed by Pt loading. The preparation process of this patent is complex, and the synthesis cost of the MOF material is high, making it unsuitable for large-scale industrial applications. Summary of the Invention
[0007] To address the above problems, this invention provides a low-Pt acidic HER catalyst based on a W, Mo, and N co-doped support, its preparation method, and its application.
[0008] To address the aforementioned technical issues, the following solutions are proposed: This invention provides a low-platinum acidic HER catalyst. This catalyst is prepared by modifying carbon black to obtain a novel carbon support (W, Mo, N co-doped) suitable for Pt loading. A small amount of Pt is then loaded onto this support to obtain a low-platinum catalyst. The prepared low-platinum catalyst exhibits superior electrocatalytic performance (10 mA / cm²) compared to commercially available catalysts with 50% Pt / C content, even with a lower Pt content. 2 The corresponding overpotential at current density is only 25mV, and 50% Pt / C at 10mA / cm 2 The overpotential at the current density is 36 mV, achieving excellent catalyst performance at a lower cost than commercially available platinum-carbon catalysts. Characterization analysis suggests that this invention modifies carbon black through chemical doping. The incorporated W and Mo nanoclusters form a heterostructure with the subsequently supported Pt particles, resulting in electron redistribution at the interface and improving the catalyst's electrocatalytic performance.
[0009] The preparation method of the low-Pt acidic HER catalyst based on W, Mo, and N co-doped support of the present invention includes the following steps: S1. The carbon source, nitrogen source, tungsten source and molybdenum source are mixed and ball-milled to obtain a mixed powder; S2. The obtained mixed powder is pyrolyzed under a protective atmosphere, and the resulting product is ground to obtain W, Mo and N doped modified carbon support. S3. Disperse an appropriate amount of doped and modified carbon support in a solvent, add a platinum source solution, mix evenly, and then reflux. S4. After the condensation and reflux are completed, perform solid-liquid separation, washing, and drying to obtain the final product.
[0010] In the preferred step S1, the nitrogen source is C3N4 and / or dicyandiamine; The carbon source is at least one of conductive carbon black and graphene; The tungsten source is sodium tungstate or ammonium tungstate; the molybdenum source is sodium molybdate or ammonium molybdate.
[0011] Preferably, the mass ratio of the carbon source to the nitrogen source is 1:5 to 1:15; Tungsten and molybdenum sources were added to the prepared W, Mo, and N-doped carbon supports, with W and Mo doping amounts of 5-20 wt.% respectively.
[0012] Preferably, in step S2, the temperature for pyrolysis is 350-900℃, and the pyrolysis time is 3-8 hours. More preferably, the pyrolysis is a staged pyrolysis; the staged pyrolysis is as follows: first, the temperature is raised to 200-400℃ and held for 1-3 hours, then the temperature is raised to 600-700℃ and held for 1-3 hours, and finally the temperature is raised to 800-900℃ and held for 1-2 hours. The protective atmosphere is nitrogen or an inert gas atmosphere.
[0013] Preferably, in step S1, the mixing ball milling is wet ball milling; the solvent used in the wet ball milling is anhydrous ethanol; and the wet ball milling time is 30 min to 2 h.
[0014] Preferably, in step S3, the mass ratio of the doped and modified carbon support to the volume ratio of the solvent used is 1:1 to 1:2 mg / mL; the solvent is ethylene glycol.
[0015] Preferably, in step S3, the platinum source solution is a chloroplatinic acid solution; the concentration of the platinum source solution is 2-8 mmol; and the platinum source is added according to the Pt loading in the final catalyst being 1-10 wt.%.
[0016] Preferably, in step S3, the temperature of the condensation reflux is 120-180℃, and the condensation reflux time is 1-3h.
[0017] As a general inventive concept, the present invention also provides a catalyst prepared by the above-described preparation method.
[0018] As a general inventive concept, the present invention also provides an application of the above-mentioned catalyst in water electrolysis, more specifically, the catalyst can be applied to hydrogen evolution in water electrolysis.
[0019] Compared with the prior art, the present invention has the following beneficial effects: The preparation method of this invention is simple, easy to implement, and readily scalable for large-scale production. It is low in cost, and the prepared low-platinum HER catalyst exhibits excellent HER electrochemical performance and stability in acidic electrolytes. Tested under 0.5 M H₂SO₄, it shows a lower overpotential and superior stability compared to commercial platinum-carbon catalysts. Even with a Pt content only 1 / 7 that of commercial platinum-carbon, the prepared low-platinum catalyst still exhibits superior electrocatalytic performance. The W and Mo nanoclusters doped into the carbon black form a heterostructure with the Pt particles, resulting in a synergistic effect between Pt and W / Mo. This optimizes the electronic structure and charge / mass transfer performance of the catalyst during the catalytic process. Furthermore, the synergistic effect effectively reduces the adsorption energy of hydrogen on the catalyst surface, bringing the adsorption Gibbs free energy of hydrogen close to the ideal value of zero, thereby promoting the HER catalytic performance of the catalyst. Attached Figure Description
[0020] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0021] Figure 1 The graph shows the HER performance of the catalysts in Examples 2, Comparative Examples 1-4, and a commercial 50% Pt / C catalyst tested under 0.5 M H2SO4, where (a) corresponds to a catalyst loading of 0.4 mg. catalyst / cm 2 (b) Corresponding catalyst loading of 20 µg Pt / cm 2 .
[0022] Figure 2 The figures show the HER performance of Examples 2-4 and the commercial 50% Pt / C catalyst tested at 0.5 M H2SO4, where (a) corresponds to a catalyst loading of 0.4 mg. catalyst / cm 2 (b) Corresponding catalyst loading of 20 µg Pt / cm 2 .
[0023] Figure 3 The graph shows the HER performance of catalysts with different Pt contents prepared in Examples 1-2, Examples 6-8, and commercial 50% Pt / C catalysts, tested under 0.5 M H2SO4. (a) corresponds to a catalyst loading of 20 µg. Pt / cm 2 (b) corresponds to a catalyst loading of 0.04 mg.catalyst / cm 2 .
[0024] Figure 4 The graph shows a comparison of the electrochemical performance of the catalysts prepared in Example 5 and Comparative Example 1 with a commercially available 50% Pt / C catalyst, where (a) corresponds to a catalyst loading of 0.4 mg. catalyst / cm 2 (b) The catalyst loading is 20 µg Pt / cm 2 .
[0025] Figure 5 The graph shows a comparison of the stability of the catalyst prepared in Example 2 and a commercial 50% Pt / C catalyst in 0.5 M H2SO4, where (a) represents the stability at 10 mA / cm². 2 (a) Stability was tested at current density for 12 hours; (b) at 100 mA / cm². 2 Stability was tested at current density for 12 hours; (c) is 10 mA / cm. 2 Stability was tested for 40 hours at current density.
[0026] Figure 6 The images shown are TEM images of the W, Mo, and N doped carbon support of Example 2 at different magnifications.
[0027] Figure 7 The images shown are TEM images of the catalysts prepared in Examples 1 and 2, where (a) and (b) are TEM images of the catalyst in Example 1, and (c) and (d) are TEM images of the catalyst in Example 2.
[0028] Figure 8 This is a schematic diagram of the microstructure of the WMoN-doped modified carbon support and Pt particles in the catalyst prepared for this invention. Detailed Implementation
[0029] This invention provides a method for preparing a low-Pt acidic HER catalyst based on a W, Mo, N co-doped support, comprising the following steps: S1. The carbon source, nitrogen source, tungsten source and molybdenum source are mixed and ball-milled to obtain a mixed powder; S2. The obtained mixed powder is pyrolyzed under a protective atmosphere, and the resulting product is ground to obtain W, Mo and N doped modified carbon support. S3. Disperse an appropriate amount of doped and modified carbon support in a solvent, add a platinum source solution, mix evenly, and then reflux. S4. After the condensation and reflux are completed, perform solid-liquid separation, washing, and drying to obtain the final product.
[0030] In some preferred embodiments, in step S1, the nitrogen source is C3N4 and / or dicyandiamine.
[0031] In some preferred embodiments, in step S1, the carbon source is at least one of conductive carbon black and graphene, and the conductive carbon black includes XC-72, XC-72R, etc.
[0032] In some preferred embodiments, in step S1, the tungsten source is sodium tungstate or ammonium tungstate; the molybdenum source is sodium molybdate or ammonium molybdate.
[0033] In some preferred embodiments, the mass ratio of the carbon source to the nitrogen source is 1:5 to 1:15. When this ratio is too high or too low, it will affect the performance of the catalyst.
[0034] In some preferred embodiments, the tungsten source and molybdenum source are added to the prepared W, Mo, N-doped modified carbon support, with each of the W and Mo doping amounts being 5-20 wt.%.
[0035] In some embodiments, in step S2, the pyrolysis temperature is 350-900℃, and the pyrolysis time is 3-8 hours. In some preferred embodiments, in step S3, the pyrolysis is a staged pyrolysis, with the process parameters being: heating to 200-400℃ and holding for 1-3 hours, then heating to 600-700℃ and holding for 1-3 hours, and finally heating to 800-950℃ and holding for 1-2 hours. Excessive temperature can easily lead to metal particle agglomeration, while insufficient temperature may result in insufficient activity of the catalyst support material, affecting catalyst performance. In some embodiments, in step S2, during the pyrolysis process, the heating rate is 2-5℃ / min, and the protective gas flow rate is 30-100 ml / min; the protective gas can be nitrogen or an inert gas such as argon.
[0036] In some preferred embodiments, in step S1, the mixing ball milling is wet ball milling; the solvent used in the wet ball milling is anhydrous ethanol; the wet ball milling time is 30 min to 2 h; after wet ball milling, the mixed powder is dried, and the drying can be done by, for example, natural air drying, which does not consume energy, or other drying methods can also be used.
[0037] In some preferred embodiments, in step S3, the mass ratio of the doped and modified carbon support to the solvent volume is 1:1-1:2 mg / mL. If this ratio is too low, it will lead to the aggregation of Pt particles, affecting the high dispersion of nano-Pt; if the ratio is too high, it will easily result in insufficient Pt reduction. In some preferred embodiments, the solvent used is ethylene glycol.
[0038] In some preferred embodiments, in step S3, the platinum source solution is a chloroplatinic acid solution; the concentration of the platinum source solution is 2-8 mmol / L; the platinum source is added according to the Pt loading in the final catalyst being 1-10 wt.%; when the concentration or loading of the platinum source solution is too high, it is easy to form larger Pt particles, which will lead to the deterioration of the catalyst performance.
[0039] In some preferred embodiments, in step S3, the reflux temperature is 120-180℃ and the reflux time is 1-3h. If the reflux temperature is too high or the reflux time is too short, the reduction may be insufficient. If the reflux temperature is too high or the time is too long, the Pt particles will be too large and affect the electrocatalytic performance of the catalyst.
[0040] In some preferred embodiments, in step S3, the dispersion is ultrasonic dispersion; In some preferred embodiments, in step S4, the drying is vacuum drying; the temperature of the vacuum drying is 60-80℃.
[0041] As another objective of this invention, this invention also provides a low-Pt acidic HER catalyst based on a W, Mo, N co-doped support, which is prepared by the preparation method described above.
[0042] As another object of the present invention, it is also provided to provide an application of the aforementioned catalyst in water electrolysis, more specifically, the catalyst can be applied to hydrogen evolution in water electrolysis.
[0043] To facilitate understanding of the present invention, the invention will be described more fully and in detail below with reference to the accompanying drawings and preferred embodiments, but the scope of protection of the present invention is not limited to the following specific embodiments.
[0044] Example 1 (1) Take 0.4g of carbon black XC-72R, 5g of dicyandiamine, weigh 0.15g of sodium tungstate and 0.1g of sodium molybdate and place them in a ball mill jar. Add an appropriate amount of anhydrous ethanol and ball mill for 1h.
[0045] (2) After ball milling, place the ball milling jar in a fume hood to dry, then collect the powder sample and perform programmed temperature pyrolysis under an argon atmosphere (heating rate 5℃ / min, argon gas flow rate 50ml / min, pyrolysis at 350℃ for 3h, then heat to 650℃ for 3h, and finally heat to 900℃ for 1h) to obtain the catalyst support 20%W10%Mo-NC.
[0046] (3) Take a portion of WMo-NC and add the corresponding amount of ethylene glycol according to the ratio of WMo-NC (mg): ethylene glycol (ml) = 1:1. Sonicate in an ultrasonic bath for 30 min. Then transfer the black suspension to a flask and place it in an oil bath for stirring. At the same time, add a Pt-containing solution (prepared 5 mmol / L chloroplatinic acid aqueous solution) according to the theoretical Pt loading of 5 wt.% in the final catalyst. Stir at room temperature for 30 min, then reflux at 140℃ for 1 h. After reflux, filter the solution after the reaction has cooled down and wash it with anhydrous ethanol. Then transfer the filter membrane to a vacuum drying oven and dry it overnight at 70℃ to obtain the catalyst, which is labeled as sample 1.
[0047] Example 2 (1) Take 0.4g of carbon black XC-72R, 5g of dicyandiamine, weigh 0.15g of sodium tungstate and 0.1g of sodium molybdate and place them in a ball mill jar. Add an appropriate amount of anhydrous ethanol and ball mill for 1h.
[0048] (2) After ball milling, place the ball milling jar in a fume hood to dry, then collect the powder sample and perform programmed temperature pyrolysis under an argon atmosphere (heating rate 5℃ / min, argon gas flow rate 50ml / min, pyrolysis at 350℃ for 3h, then heat to 650℃ for 3h, and finally heat to 900℃ for 1h) to obtain the catalyst support 20%W10%Mo-NC.
[0049] (3) Take a portion of WMo-NC and add the corresponding amount of ethylene glycol according to the ratio of WMo-NC (mg): ethylene glycol (ml) = 1:1. Sonicate in an ultrasonic bath for 30 min. Then transfer the black suspension to a flask and place it in an oil bath for stirring. At the same time, add a Pt-containing solution (prepared 5 mmol / L chloroplatinic acid aqueous solution) according to the theoretical Pt loading of 7.5 wt.% in the final catalyst. Stir at room temperature for 30 min, then reflux at 140℃ for 1 h. After reflux, filter the solution after the reaction has cooled down and wash it with anhydrous ethanol. Then transfer the filter membrane to a vacuum drying oven and dry it overnight at 70℃ to obtain the final catalyst, which is labeled as sample 2.
[0050] Example 3 (1) Take 0.4g of carbon black XC-72R, 5g of dicyandiamine, weigh 0.15g of sodium tungstate and 0.05g of sodium molybdate and place them in a ball mill jar. Add an appropriate amount of anhydrous ethanol and ball mill for 1h.
[0051] (2) After ball milling, place the ball milling jar in a fume hood to dry, then collect the powder sample and perform programmed temperature pyrolysis under an argon atmosphere (heating rate 5℃ / min, argon gas flow rate 50ml / min, pyrolysis at 350℃ for 3h, then heat to 650℃ for 3h, and finally heat to 900℃ for 1h) to obtain the catalyst support 20%W5%Mo-NC.
[0052] (3) Take a portion of WMo-NC and add the corresponding amount of ethylene glycol according to the ratio of WMo-NC (mg): ethylene glycol (ml) = 1:1. Sonicate in an ultrasonic bath for 30 min. Then transfer the black suspension to a flask and place it in an oil bath for stirring. At the same time, add a Pt-containing solution (prepared 5 mmol / L chloroplatinic acid aqueous solution) with a theoretical Pt loading of 7.5 wt.% in the final catalyst. Stir at room temperature for 30 min, then reflux at 140℃ for 1 h. After reflux, filter the solution after the reaction has cooled down and wash it with anhydrous ethanol. Then transfer the filter membrane to a vacuum drying oven and dry it overnight at 70℃ to obtain the final catalyst, which is labeled as sample 3.
[0053] Example 4 (1) Take 0.4g of carbon black XC-72R, 5g of dicyandiamine, weigh 0.15g of sodium tungstate and 0.2g of sodium molybdate and place them in a ball mill jar. Add an appropriate amount of anhydrous ethanol and ball mill for 1h.
[0054] (2) After ball milling, place the ball milling jar in a fume hood to dry, then collect the powder sample and perform programmed temperature pyrolysis under an argon atmosphere (heating rate 5℃ / min, argon gas flow rate 50ml / min, pyrolysis at 350℃ for 3h, then heat to 650℃ for 3h, and finally heat to 900℃ for 1h) to obtain the catalyst support 20%W20%Mo-NC.
[0055] (3) Take a portion of WMo-NC and add the corresponding amount of ethylene glycol according to the ratio of WMo-NC (mg): ethylene glycol (ml) = 1:1. Sonicate in an ultrasonic bath for 30 min. Then transfer the black suspension to a flask and place it in an oil bath for stirring. At the same time, add a Pt-containing solution (prepared 5 mmol / L chloroplatinic acid aqueous solution) according to the theoretical Pt loading of 7.5 wt.% in the final catalyst. Stir at room temperature for 30 min, then reflux at 140℃ for 1 h. After reflux, filter the solution after the reaction has cooled down and wash it with anhydrous ethanol. Then transfer the filter membrane to a vacuum drying oven and dry it overnight at 70℃ to obtain the final catalyst, which is labeled as sample 4.
[0056] Example 5 (1) Take 0.4g of carbon black XC-72R, 2.5g of C3N4, weigh 0.15g of sodium tungstate and 0.1g of sodium molybdate and place them in a ball mill jar. Add an appropriate amount of anhydrous ethanol and ball mill for 1h.
[0057] (2) After ball milling, place the ball milling jar in a fume hood to dry, then collect the powder sample and perform programmed temperature pyrolysis under an argon atmosphere (heating rate 5℃ / min, argon gas flow rate 50ml / min, pyrolysis at 350℃ for 3h, then pyrolysis at 650℃ for 3h, and finally pyrolysis at 900℃ for 1h) to obtain the catalyst support 20%W10%Mo-NC(C3N4).
[0058] (3) Take a portion of WMo-C3N4 and add the corresponding amount of ethylene glycol according to the ratio of WMo-C3N4 (mg): ethylene glycol (ml) = 1:1. Sonicate in an ultrasonic bath for 30 min. Then transfer the black suspension to a flask and place it in an oil bath for stirring. At the same time, add a Pt-containing solution (prepared 5 mmol / L chloroplatinic acid aqueous solution) according to the theoretical Pt loading of 7.5 wt.% in the final catalyst. Stir at room temperature for 30 min, then reflux at 140℃ for 1 h. After reflux, filter the solution after the reaction has cooled down and wash it with anhydrous ethanol. Then transfer the filter membrane to a vacuum drying oven and dry it overnight at 70℃ to obtain the final catalyst, which is labeled as sample 5.
[0059] Comparative Example 1 Take 0.4 g of carbon black XC-72R, and add the corresponding amount of ethylene glycol according to the ratio of XC-72R (mg): ethylene glycol (ml) = 1:1. Sonicate the mixture in an ultrasonic bath for 30 min. Then transfer the black suspension to a flask, place it in an oil bath, and stir. Simultaneously, add a Pt-containing solution (pre-prepared 5 mmol / L chloroplatinic acid aqueous solution) according to the theoretical Pt loading of 7.5 wt.% in the final catalyst. Stir at room temperature for 30 min, then reflux at 140℃ for 1 h. After reflux, allow the reaction to cool, filter, and wash with anhydrous ethanol. Transfer the filter membrane to a vacuum drying oven and dry overnight at 70℃ to obtain the final catalyst, labeled as sample 6.
[0060] Comparative Example 2 (1) Take 0.4g of carbon black XC-72R and 5g of dicyandiamine, place them in a ball mill jar, add an appropriate amount of anhydrous ethanol and ball mill for 1h.
[0061] (2) After ball milling, place the ball milling jar in a fume hood to dry, then collect the powder sample and perform programmed temperature pyrolysis under an argon atmosphere (heating rate 5℃ / min, argon gas flow rate 50ml / min, pyrolysis at 350℃ for 3h, then heat to 650℃ for 3h, and finally heat to 900℃ for 1h) to obtain the catalyst support NC.
[0062] (3) Take a portion of NC, and take the corresponding amount of ethylene glycol according to the ratio of NC (mg): ethylene glycol (ml) = 1:1. Sonicate in an ultrasonic bath for 30 min, then transfer the black suspension to a flask, place it in an oil bath and stir. At the same time, add a Pt-containing solution (prepared 5 mmol / L chloroplatinic acid aqueous solution) according to the theoretical Pt loading of 7.5 wt.% in the final catalyst. Stir at room temperature for 30 min, then reflux at 140℃ for 1 h. After reflux, filter after the reaction has cooled down, wash with anhydrous ethanol, and then transfer the filter membrane to a vacuum drying oven and dry at 70℃ overnight to obtain the final catalyst, labeled as sample 7.
[0063] Comparative Example 3 (1) Take 0.4g of carbon black XC-72R, 5g of dicyandiamine, and 0.15g of sodium tungstate and place them in a ball mill jar. Add an appropriate amount of anhydrous ethanol and ball mill for 1h.
[0064] (2) After ball milling, place the ball milling jar in a fume hood to dry, then collect the powder sample and perform programmed temperature pyrolysis under an argon atmosphere (heating rate 5℃ / min, argon gas flow rate 50ml / min, pyrolysis at 350℃ for 3h, then heat to 650℃ for 3h, and finally heat to 900℃ for 1h) to obtain the catalyst support 20%WNC.
[0065] (3) Take a portion of WNC, and take the corresponding amount of ethylene glycol according to the ratio of WNC (mg): ethylene glycol (ml) = 1:1. Sonicate in an ultrasonic bath for 30 min, then transfer the black suspension to a flask, place it in an oil bath and stir. At the same time, add a Pt-containing solution (prepared 5 mmol / L chloroplatinic acid aqueous solution) according to the theoretical Pt loading of 7.5 wt.% in the final catalyst. Stir at room temperature for 30 min, then reflux at 140℃ for 1 h. After reflux, wait for the reaction to cool down and then filter, wash with anhydrous ethanol, then transfer the filter membrane to a vacuum drying oven and dry at 70℃ overnight to obtain the final catalyst, labeled as sample 8.
[0066] Comparative Example 4 (1) Take 0.4g of carbon black XC-72R, 5g of dicyandiamine, and 0.05g of sodium molybdate and place them in a ball mill jar. Add an appropriate amount of anhydrous ethanol and ball mill for 1h.
[0067] (2) After ball milling, place the ball milling jar in a fume hood to dry, then collect the powder sample and perform programmed temperature pyrolysis under an argon atmosphere (heating rate 5℃ / min, argon gas flow rate 50ml / min, pyrolysis at 350℃ for 3h, then heat to 650℃ for 3h, and finally heat to 900℃ for 1h) to obtain the catalyst support 10%Mo-NC.
[0068] (3) Take a portion of Mo-NC and add the corresponding amount of ethylene glycol according to the ratio of Mo-NC (mg): ethylene glycol (ml) = 1:1. Sonicate in an ultrasonic bath for 30 min. Then transfer the black suspension to a flask and place it in an oil bath for stirring. At the same time, add a Pt-containing solution (prepared 5 mmol / L chloroplatinic acid aqueous solution) according to the theoretical Pt loading of 7.5 wt.% in the final catalyst. Stir at room temperature for 30 min, then reflux at 140℃ for 1 h. After reflux, filter the solution after the reaction has cooled down and wash it with anhydrous ethanol. Then transfer the filter membrane to a vacuum drying oven and dry it overnight at 70℃ to obtain the final catalyst, labeled as sample 9.
[0069] Example 6 The only difference between this embodiment and Example 1 is that in step (3), the catalyst prepared by using a 5 mmol / L aqueous solution of chloroplatinic acid with a theoretical Pt loading of 1 wt.% in the final catalyst is labeled as Sample 10.
[0070] Example 7 The only difference between this embodiment and Example 1 is that in step (3), the catalyst prepared by using a 5 mmol / L aqueous solution of chloroplatinic acid with a theoretical Pt loading of 2.5 wt.% in the final catalyst is labeled as Sample 11.
[0071] Example 8 The only difference between this embodiment and Example 1 is that in step (3), the catalyst prepared by using a 5 mmol / L aqueous solution of chloroplatinic acid with a theoretical Pt loading of 10 wt.% in the final catalyst is labeled as Sample 12.
[0072] Performance testing: 1. Preparation of catalyst ink: Weigh 4 mg of the catalyst to be tested, and prepare it by adding 4 mg catalyst + 250 μL ethanol + 250 μL isopropanol + 10 μL 5% Nafion solution. Sonicate in an ultrasonic bath for more than 1 hour. After homogenization, electrochemical testing can be performed.
[0073] 2. Drop Electrode: The electrochemical performance of the catalyst was tested using an L-shaped glassy carbon electrode tip with a diameter of 5 mm. An appropriate amount of ultrasonically dispersed catalyst ink was dropped onto the surface of a platinum-carbon electrode (the catalyst loading on the glassy carbon electrode was controlled to be 0.4 mg). catalyst / cm 2 Or 20µg Pt / cm 2 Then, after it dries naturally, it is tested.
[0074] 3. Electrochemical Performance Testing: Three-electrode testing was performed using a Chenhua electrochemical workstation. The prepared glassy carbon electrode tip was placed in a 0.5 M H₂SO₄ solution, with a silver chloride electrode as the reference electrode and a graphite electrode as the counter electrode. The catalyst was first activated by at least 40 cycles, with a scan range of -0.6 to -0.1 V and a scan rate of 100 mV / s. Subsequently, LSV testing was performed, with a test range of -0.6 to -0.1 V and a scan rate of 10 mV / s. (All electrochemical data in this application have been corrected for IR data.) 4. Catalyst stability test: A constant current test was used, with the current controlled at 0.0019625V. Tests were conducted at 0.019625V for different durations, yielding current densities of 10 mA / cm². 2 100mA / cm 2 Stability test data at different current densities over different times.
[0075] It is worth noting that when using W or Mo doping alone on a carbon matrix, the applicant explored different doping amounts of W and Mo. When using W doping alone, the catalyst prepared with a doping amount of 20 wt.% W showed the best performance, while when using Mo doping alone, the catalyst prepared with a doping amount of 10 wt.% Mo showed the best performance. Therefore, among the above comparative examples, only the optimal doping cases, Comparative Example 3 and Comparative Example 4, are shown.
[0076] Figure 1 The graphs show the overpotential test results for Examples 2, Comparative Examples 1-4, and the commercial 50% Pt / C catalyst. For easy comparison with 50% commercial platinum-carbon, two different loading methods were used in the tests: 0.04 mg... catalyst / cm 2 and 20µg Pt / cm 2Specific data are shown in Tables 1 and 2. Comparison of the data from Sample 6 (Comparative Example 1) and Sample 7 (Comparative Example 2) reveals that N doping on carbon black effectively promotes the electrocatalytic performance of the catalyst, reducing the overpotential. Comparative analysis of the data from Sample 7 (Comparative Example 2), Sample 8 (Comparative Example 3), and Sample 9 (Comparative Example 4) shows that, in addition to N doping, individual doping with W and Mo can effectively promote the electrocatalytic performance of the catalyst. Comparative analysis of the data from Sample 8 (Comparative Example 3), Sample 9 (Comparative Example 4), and Sample 2 (Example 2) reveals that when W, Mo, and N are simultaneously doped onto carbon, the catalyst prepared by loading 7.5% Pt onto the resulting catalyst support exhibits superior electrocatalytic performance. This further demonstrates a synergistic effect between W, Mo, and Pt, leading to electron redistribution at the interface and promoting the electrocatalytic performance of the catalyst.
[0077] The HER overpotential of the catalysts in Examples 2-4 and a commercial 50% Pt / C catalyst was tested at 0.5 M H2SO4 with a catalyst loading of 20 µg. Pt / cm 2 and 0.04mg catalyst / cm 2 The corresponding electrochemical performance graph is as follows Figure 2 As shown in (a) and (b), the data results indicate that the prepared W, Mo, N co-doped carbon support exhibits the best electrochemical performance when the W:Mo ratio is 2:1, i.e., 20%W 10%Mo, under the same W loading (20%).
[0078] Figure 3 The graph shows the HER performance of catalysts with different Pt contents prepared in Examples 1-2, Examples 6-8, and commercial 50% Pt / C catalysts, tested under 0.5 M H2SO4. The catalyst loading was 20 µg. Pt / cm 2 and 0.04mg catalyst / cm 2 The corresponding HER performance graph is as follows Figure 3 As shown in (a) and (b), catalysts with different Pt loadings (1%, 2.5%, 5%, 7.5% and 10%) were explored.
[0079] Figure 4 The graph shows a comparison of the electrochemical performance of the catalysts prepared in Example 5 and Comparative Example 1 with a commercially available 50% Pt / C catalyst. (a) and (b) represent catalysts with a loading of 0.4 mg, respectively. catalyst / cm 2 and 20µg Pt / cm 2 The corresponding electrochemical performance comparison chart. Combined with... Figure 4 and Figure 5 It can be seen that after replacing dicyandiamine with C3N4, the prepared low-platinum catalyst still has better electrochemical performance than commercial platinum-carbon catalyst.
[0080] Figure 5 This is a stability comparison chart of the catalyst prepared in Example 2 and a commercial 50% Pt / C catalyst in 0.5 M H2SO4, with a catalyst loading of 20 µg. Pt / cm 2 Where (a) is 10 mA / cm 2 (a) Stability was tested at current density for 12 hours; (b) at 100 mA / cm². 2 Stability was tested at current density for 12 hours; (c) is 10 mA / cm. 2 Stability was tested at current density for 40 hours. The test results show that the electrochemical stability of the catalyst prepared in Example 2 is superior to that of commercial catalysts.
[0081] Figure 6 The images shown in Figure (b) are TEM images of the carbon support modified with W, Mo, and N doping in Example 2 at different magnifications. It can be clearly seen from Figure (b) that the small particles on the carbon material are WMo nanoclusters, indicating that W and Mo are successfully embedded in the carbon material and are uniformly dispersed on the carbon as nanoclusters of 2-3 nm in size.
[0082] Figure 7 TEM images of the catalysts prepared in Examples 1 and 2 are shown, where (a) and (b) correspond to the catalyst of Example 1, and (c) and (d) correspond to the catalyst of Example 2. The red circles enclose WMo nanoclusters, and the red boxes show Pt particles. It can be seen that the Pt particles are supported on the WMo nanoclusters-doped carbon material, and some Pt particles are directly supported on the WMo nanoclusters on the carbon material. Combined with the aforementioned electrochemical performance, it can be concluded that there is a synergistic effect between W, Mo, and Pt, which promotes electrochemical performance. Therefore, it is speculated that W, Mo nanoclusters and Pt may form a heterojunction structure, thereby generating electron redistribution at the interface to achieve a synergistic effect and optimize the electronic structure and charge / mass transfer performance of the catalyst during the catalytic process. The microstructure of the WMoN-doped modified carbon support and Pt particles in the catalyst prepared in this invention is illustrated below. Figure 8 As shown, this structure can change the electron configuration at the interface, thereby further enhancing the electrocatalytic performance of the catalyst.
[0083] Table 1. HER overpotential data of the catalysts in Example 2 and Comparative Examples 1-4 tested at 0.5 M H2SO4, with a catalyst loading of 0.04 mg. catalyst / cm 2 Table 2. HER overpotential data of the catalysts in Examples 2 and Comparative Examples 1-4 tested at 0.5 M H2SO4, with a catalyst loading of 20 µg. Pt / cm 2 In summary, this invention modifies the traditional carbon black support by doping W, Mo, and N into the catalyst support material, and then loads a small amount of Pt onto it. The resulting low-platinum catalyst exhibits superior electrocatalytic performance compared to commercial platinum-carbon catalysts, even with a Pt content only 1 / 7 that of commercial platinum-carbon catalysts. TEM characterization reveals that WMo nanoclusters with a particle size of 2-3 nm are uniformly dispersed on the carbon support. These uniformly dispersed WMo nanoclusters form a heterojunction structure with the subsequently loaded Pt particles, resulting in electron redistribution at the interface and achieving a synergistic effect. This optimizes the electronic structure and charge / mass transfer performance of the catalyst during the catalytic process. Furthermore, the synergistic effect effectively reduces the adsorption energy of hydrogen on the catalyst surface, bringing the adsorption Gibbs free energy of hydrogen close to the ideal value of zero, thus promoting the electrocatalytic performance of the catalyst.
[0084] The prepared low-platinum HER catalyst exhibits excellent electrocatalytic performance in acidic electrolytes. Tested at 0.5 M H₂SO₄, it shows a lower overpotential and superior stability compared to commercial platinum-carbon catalysts. (10 mA / cm) 2 The corresponding overpotential at the current density is 25mV (0.4mgcatalyst / cm). 2 (Load), superior to 50% of commercial platinum-carbon (10mA / cm) 2 The overpotential at the current density is 36 mV. It is clear that, under the same 0.4 mg catalyst loading, the 50% Pt / C catalyst, containing nearly 7 times the platinum content of the low-platinum catalyst (20% W, 10% Mo, 7.5% Pt) of this application, still exhibits a better overpotential. This application also prepared the XC-72R 7.5% Pt catalyst with a 7.5% Pt content. Comparatively, the synthesized low-platinum catalyst also exhibits better electrocatalytic activity (10 mA / cm²). 2 The corresponding overpotential at the current density is 36mV, and for XC-72R7.5%Pt at 10mA / cm²... 2 The corresponding overpotential at the current density is 42mV. (100mA / cm) 2 The same applies at current densities (the prepared low-platinum catalyst at 100 mA / cm). 2 The overpotential at current density is 42mV, which is better than that of commercial platinum-carbon (50mV).
[0085] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A method for preparing a low-Pt acidic HER catalyst based on a W, Mo, N co-doped support, characterized in that, Includes the following steps: S1. A carbon source, a nitrogen source, a tungsten source, and a molybdenum source are mixed and ball-milled to obtain a mixed powder; the nitrogen source is C3N4 and / or dicyandiamine. S2. The obtained mixed powder is subjected to staged heating pyrolysis under a protective atmosphere, and the obtained product is ground to obtain W, Mo and N doped modified carbon support. The staged heating pyrolysis is as follows: first, the temperature is raised to 200-400℃ and held for 1-3 hours, then the temperature is raised to 600-700℃ and held for 1-3 hours, and finally the temperature is raised to 800-900℃ and held for 1-2 hours. S3. Disperse an appropriate amount of doped and modified carbon support in a solvent, add a platinum source solution, mix evenly, and then reflux. S4. After the condensation and reflux are completed, perform solid-liquid separation, washing, and drying to obtain the final product.
2. The preparation method of the low-Pt acidic HER catalyst based on a W, Mo, N co-doped support as described in claim 1, characterized in that, In step S1, the carbon source is at least one of conductive carbon black and graphene; the tungsten source is sodium tungstate or ammonium tungstate; and the molybdenum source is sodium molybdate or ammonium molybdate.
3. The preparation method of the low-Pt acidic HER catalyst based on a W, Mo, N co-doped support as described in claim 1, characterized in that, The mass ratio of the carbon source to the nitrogen source is 1:5 to 1:15; Tungsten and molybdenum sources were added to the prepared W, Mo, and N-doped carbon supports, with W and Mo doping amounts of 5-20 wt.% respectively.
4. The preparation method of the low-Pt acidic HER catalyst based on a W, Mo, N co-doped support as described in claim 1, characterized in that, In step S2, the protective atmosphere is a nitrogen atmosphere.
5. The method for preparing a low-Pt acidic HER catalyst based on a W, Mo, N co-doped support as described in claim 1, characterized in that, In step S2, the protective atmosphere is an inert gas atmosphere.
6. The method for preparing the low-Pt acidic HER catalyst based on a W, Mo, N co-doped support as described in claim 1, characterized in that, In step S1, the mixing ball milling is a wet ball milling; the solvent used in the wet ball milling is anhydrous ethanol; and the wet ball milling time is 30 min to 2 h.
7. The method for preparing a low-Pt acidic HER catalyst based on a W, Mo, N co-doped support as described in claim 1, characterized in that, In step S3, the mass ratio of the doped and modified carbon support to the volume ratio of the solvent used is 1:1-1:2 mg / mL; the solvent is ethylene glycol.
8. The method for preparing the low-Pt acidic HER catalyst based on a W, Mo, N co-doped support as described in claim 1, characterized in that, In step S3, the platinum source solution is a chloroplatinic acid solution; the concentration of the platinum source solution is 2-8 mmol / L; and the platinum source is added according to the Pt loading in the final catalyst being 1-10 wt.%.
9. The method for preparing a low-Pt acidic HER catalyst based on a W, Mo, N co-doped support as described in claim 1, characterized in that, In step S3, the temperature of the condensation reflux is 120-180℃; the condensation reflux time is 1-3h.
10. A low-Pt acidic HER catalyst based on a W, Mo, N co-doped support, characterized in that, Prepared using the preparation method described in any one of claims 1-9.
11. The application of the low-Pt acidic HER catalyst based on W, Mo, N co-doped support as described in claim 10 in water electrolysis.
Citation Information
Patent Citations
Pt atomic cluster loaded WO3 nanosheet hydrogen evolution reaction catalyst and preparation method thereof
CN111298790A
Process for producing carbon-comprising support
CN103118779A